2009
DOI: 10.1038/sj.bjc.6605235
|View full text |Cite
|
Sign up to set email alerts
|

The needs of patients with advanced, incurable cancer

Abstract: BACKGROUND: Limited research has investigated the specific needs of patients with advanced incurable cancer. The aim of this study was to describe the prevalence of perceived needs among this population. METHODS: Medical specialists from two regions in New South Wales, Australia, identified patients with advanced, incurable cancer, who were estimated to have a life expectancy of o2 years and were not receiving formal palliative care. Of the 418 eligible patients, 246 (59%) consented to participate. Consenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
3
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 36 publications
11
144
3
13
Order By: Relevance
“…Some of the reviewed studies illustrated clear dissociations between reported 'problems' versus 'needs' [3]. In areas where patients appear to be struggling or suffering but do not identify 'needs' for supportive care, divergent interpretations could be made.…”
Section: Assessment Of Unmet Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the reviewed studies illustrated clear dissociations between reported 'problems' versus 'needs' [3]. In areas where patients appear to be struggling or suffering but do not identify 'needs' for supportive care, divergent interpretations could be made.…”
Section: Assessment Of Unmet Needsmentioning
confidence: 99%
“…Studies also tended to exclude individuals on the basis of language ability. To improve generalisability, some studies used random sampling (e.g., [37]), or compared responders with non-responders (e.g., [3]) or reference populations (e.g., [8]) to gauge potential selection biases. Two of the four qualitative studies did not explicate reflexivity; it was thus not clear how extracted data were influenced by the researchers' own perspectives and positioning in these studies.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…In several cases, patients' expectations might be higher than practicable by medical professionals. Particularly cancer patients experience high levels of unmet needs, also in relation to conventional psychosocial and medical communication/information [35][36][37]. Although there are attempts to address supportive care needs of patients with cancer, assessing areas such as psychology, health system and information, physical and daily living, patient care and support, and sexuality [37], it is remarkable that spiritual and existential needs are in most cases either not recognized or even ignored.…”
Section: Addressing Spiritual Needs As An Approach In Health Carementioning
confidence: 99%
“…To achieve this goal, physicians need to know which pieces of information to convey, how to convey them, and when. 62 The majority of oncology patients indicate a desire to know their diagnosis and the extent of disease, their treatment options, and even relatively rare side effects of these treatments. 63,64 Most oncology patients also want to know their prognosis 47,64 and have rated prognostic information as the most important element of communication -more important than diagnostic disclosure or treatment information.…”
Section: 61mentioning
confidence: 99%